SOCIAL STATUS AND PROBLEMS OF FISHING COMMUNITY AT ALLAHABAD - PAYNE, A. L.; KATIHA, PRADEEP K.; SINGH, H. R.; SINGH, P. R.; PANDEY, S. K. (Journal of Indian Fisheries Association, 2015)
The paper highlights social status and sociomeconomic problems of fishermen living along the Ganga and the Yamuna at Allahabad. Since the problems of fishermen varied with respect to category (with owned boat and with hired boat) and location, significance of this variation was tested by x 2-test. The paper further emphasises on an intensive study of fishermen community to have indepth analysis of their problems and to suggest remedial measures for their upliftment.